2012
DOI: 10.1111/are.12060
|View full text |Cite
|
Sign up to set email alerts
|

In vitroAntifungal activity of essential oils fromTymbra,Origanum,Saturejaspecies and some pure compounds on the fish pathogenic fungus,Saprolegnia parasitica

Abstract: In the present study, the chemical composition and antifungal activity of the essential oils of the three Lamiaceae species, black tyme (Thymbra spicata L.), oregano (Origanum onites L.) and savory (Satureja tymbra L.) against Saprolegnia parasitica Coker strains (3) were evaluated. The composition of oils was analysed by gas chromatography/mass spectrometry (GC/MS). The major constituent of the oils was carvacrol (82.68% in Thymbra spicata, 82.24% in Origanum onites and 52.38% in Satureja tymbra). The antifun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 17 publications
1
25
0
5
Order By: Relevance
“…Numerous early studies suggested that natural products (compounds and extracts) derived from some medicinal plants have potential to be used for prevention and control against Saprolegnia (Gormez and Diler 2014; Huang et al ) found that Magnolia officinalis exhibited enhanced growth inhibition and could therefore be a valuable antifungal herbal species. Gormez and Diler () evaluated the in vitro antifungal activity of essential oils extracted from Tymbra , Origanum , and Satureja species on S. parasitica , and suggested that these essential oils have the potential to be used against S. parasitica infection in rainbow trout ( Oncorhyncus mykiss ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous early studies suggested that natural products (compounds and extracts) derived from some medicinal plants have potential to be used for prevention and control against Saprolegnia (Gormez and Diler 2014; Huang et al ) found that Magnolia officinalis exhibited enhanced growth inhibition and could therefore be a valuable antifungal herbal species. Gormez and Diler () evaluated the in vitro antifungal activity of essential oils extracted from Tymbra , Origanum , and Satureja species on S. parasitica , and suggested that these essential oils have the potential to be used against S. parasitica infection in rainbow trout ( Oncorhyncus mykiss ).…”
Section: Discussionmentioning
confidence: 99%
“…There are few comparable data in the literature of rhein, but these findings support that rhein shows promising anti-Saprolegnia properties that could be exploited as a fungicide in the prevention and control of Saprolegnia infection, while its 48 h-LC 50 to the host (grass carp) was determined to be 148.5 mg/L which indicated the safety for use of rhein for this purpose. Numerous early studies suggested that natural products (compounds and extracts) derived from some medicinal plants have potential to be used for prevention and control against Saprolegnia (Gormez and Diler 2014;Huang et al 2015) found that Magnolia officinalis exhibited enhanced growth inhibition and could therefore be a valuable antifungal herbal species. Gormez and Diler (2014) evaluated the in vitro antifungal activity of essential oils extracted from Tymbra, Origanum, and Satureja species on S. parasitica, and suggested that these essential oils have the potential to be used against S. parasitica infection in rainbow trout (Oncorhyncus mykiss).…”
Section: Discussionmentioning
confidence: 99%
“…() observed that MIC values of O. vulgare , T. vulgaris and S. montana were 100 μL mL −1 , 100 μL mL −1 , 200 μL mL −1 , respectively and all plants had a fungicidal activity at 200 μL mL −1 . Gormez and Diler () noted that MIC values of the essential oils of O. onites, S. tymbra and T. spicata for S. parasitica strains were 10 μL mL −1 , 100 μL mL −1 and 50 μL mL −1 respectively. Perrucci, Cecchini, Pretti, Cognetti, Macchioni, Flamini and Cioni () observed antifungal effects of thyme and savoury essential oils against Saprolegnia ferax .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies about the use of plant extracts against pathogenic fungi have been observed that some essential oils are capable of inhibiting the growth or even causing the death of S. parasitica at comparatively low concentrations (Khallil ; Tampieri, Galuppi, Carelle, Macchioni, Cioni & Morelli ; Sharif Rohani, Ebrahimzadeh Mosavi, Khosravi, Baba, Bahonar, Mirzargar & Mehrabi ; Udomkusonsri, Trongvanichnam, Limpoka, Klangkaew & Kusucharit ; Pirbalouti et al . ; Gormez & Diler ). In addition, several investigators have evaluated the possibility of using these natural products as fungicidal agents on fish eggs in aquaculture system (Tampieri, Carelle & Galuppi ; Pirbalouti et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation